2000
DOI: 10.1562/0031-8655(2000)072<0681:taoaah>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of 5-Aminolevulinic Acid Hexyl Ester and 5-Aminolevulinic Acid to Normal Nude Mouse Skin: Differences in Protoporphyrin IX Fluorescence Kinetics and the Role of the Stratum Corneum¶

Abstract: An important limitation of topical 5-aminolevulinic acid (ALA)-based photodetection and photodynamic therapy is that the amount of the fluorescing and photosensitizing product protoporphyrin IX (PpIX) formed is limited. The reason for this is probably the limited diffusion of ALA through the stratum corneum. A solution to this problem might be found in the use of ALA derivatives, as these compounds are more lipophilic and therefore might have better penetration properties than ALA itself. Previous studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 29 publications
3
81
1
2
Order By: Relevance
“…However, the use of He -ALA for the treatment of skin cancer is still a matter of discussion, due to the fact that He -ALA diffuses more slowly across the stratum corneum than ALA (van den Akker et al, 2000).…”
mentioning
confidence: 99%
“…However, the use of He -ALA for the treatment of skin cancer is still a matter of discussion, due to the fact that He -ALA diffuses more slowly across the stratum corneum than ALA (van den Akker et al, 2000).…”
mentioning
confidence: 99%
“…Excitation light at a wavelength of 407 nm was coupled into one arm of the birfurcated probe, enabling conduction of excitation to the skin surface and collection of the PpIX fluorescence emission via the other arm to the spectrometer. Taking into account the attenuation coefficient for skin, the 407-nm light penetrates deep enough into the skin to excite the PpIX in the epidermis and dermis (46). The fiber tip was fitted with a rubber spacer that ensured a constant fixed distance of 7 mm between the fiber and the tissue and provided optimal signal collection from the tissue.…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…At last, they concluded that pH has an important influence on the light emission and absorption of porphyrins. While penetrating into the superficial mucosal cells and applying generally and topically, 5-ALA is considered as a good route for administration as it avoids the systemic side effects and only induces local photosensitization [50,51].…”
Section: Fluorophoresmentioning
confidence: 99%